2004
DOI: 10.1248/bpb.27.1701
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Action of Cognitive Enhancers on Neuroreceptors

Abstract: No strategies for curing Alzheimer's disease have been developed yet as we do not know the exact cause of the disease. The only therapy that is available for patients is symptomatic treatment. Since Alzheimer's disease is associated with downregulation of the cholinergic system in the brain, its stimulation is expected to improve the patients' cognition, learning, and memory. Four anticholinesterases have been approved in the U.S.A. for the treatment of Alzheimer's disease patients. However, because of the inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 26 publications
1
28
0
2
Order By: Relevance
“…Specifically, it has been suggested that mechanisms other than enhancement of cholinergic function may be involved in the pharmacology of donepezil efficacy in improving cognition (Narahashi et al, 2004;Moriguchi et al, 2005). Systemic administration of donepezil has been found to increase levels of norepinephrine, dopamine, and serotonin, in addition to its effects on acetylcholine (Cuadra et al, 1994;Giacobini et al, 1996;Shearman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been suggested that mechanisms other than enhancement of cholinergic function may be involved in the pharmacology of donepezil efficacy in improving cognition (Narahashi et al, 2004;Moriguchi et al, 2005). Systemic administration of donepezil has been found to increase levels of norepinephrine, dopamine, and serotonin, in addition to its effects on acetylcholine (Cuadra et al, 1994;Giacobini et al, 1996;Shearman et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Sintomas não cognitivos presentes em casos de DA, como ansiedade e depressão, são usualmente descritos como secundários a uma disfunção nos sistemas desses neurotransmissores (Assal e Cummings, 2002;Erkinjuntti, 2002), o que torna essa hipótese ainda mais relevante. Além disso, um estudo com pacientes deprimidos, utilizando fluoxetina, citalopram e paroxetina, sugeriu a hipótese da sensibilização dos receptores "D2-like" como efeito central da ação antidepressiva dos ISRS (Narahashi, 2004).…”
Section: Discussionunclassified
“…Tacrine directly enhances acetylcholine transmission by inhibition of AChE while deprenyl will increase acetylcholine activity indirectly via improved dopamine function (Tariot et al, 1987;Piccinin et al, 1990;Mangoni et al, 1991;Molinengo and Ghi, 1997). Nefiracetam also exerts strong effects on cholinergic function and, in vitro, this nootrope has been shown to enhance neuritogenesis and NCAM PSA expression (Odumeru et al, 1997;Woodruff Pak and Hinchliffe, 1997;Oyaizu and Naharishi, 1999;Nishizaki et al, 2000;Narahashi et al, 2004). It is also likely that other transmitter systems enhancing neural activity will contribute to this neuroplastic response as previous studies have suggested activation of NMDA receptors to result in increased polysialylation in ex vivo preparations of neural tissue (Bouzioukh et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several such potential Alzheimer's treatments have been shown to augment cholinergic function. For example, the nootropic antidementia agent nefiracetam stimulates nicotinic receptors as efficiently as galantamine and donepezil, an effect that is dependent on Gs protein(s) (Nishizaki et al, 2000;Shorvon, 2001;Narahashi et al, 2004). Also, the procognitive action of the monoamine oxidase B inhibitor, l-deprenyl, in aged rats and Alzheimer's patients is thought to result from monoaminergic-driven enhancement of cholinergic function, in particular, in the hippocampus (Tariot et al, 1987;Piccinin et al, 1990;Mangoni et al, 1991;Molinengo and Ghi, 1997).…”
Section: Introductionmentioning
confidence: 99%